Links between the Prophet Muhammad (PBUH) recommended foods and disease management: A review in the light of modern super foods - Ali, Sharique A.; Parveen, Naima; Ali, Ayesha S. (International Journal of Health Sciences, 2018)
Nutrition and other bioactive natural products present in specific foods within a balanced diet play an indispensable role in maintaining and promoting human health. Plants are rich sources of a balanced nutrition because of high content of bioactive products; hence, most of them recently have acquired the status of superfoods. It has been used since ancient times for the treatment of various ailments, and these traditional medicines still remain as one of the most affordable and easily accessible sources of treatment in the primary health-care system. The scientifically based use of these superfoods date back to the era of Prophet Muhammad along with other historical uses of plant products. Prescription of a large number of herbal foods such as dates, pomegranate, olives, figs, grapes, and black seeds was successfully proposed by him. These recently have become superfoods with their powerful healing properties and act as favorable dietary interventions for disease prevention as well as for the good maintenance of health. The use of these foods as ingredients of natural origin with fewer side effects seems to be more favorable than the chemical treatment, which is often complicated. The present review is an attempt to provide a brief survey of the literature on scientifically based significance of these superfoods carried out by various researchers and exploration of a wide spectrum of their pharmacological actions which include antidiabetic, anticancer, immune modulator, analgesic, anti-inflammatory, and hepatoprotective properties.